2022
DOI: 10.3390/ma15051804
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Octadecyltrimethoxysilane-Based Coatings on Aluminum Alloy Surface

Abstract: Long-term stability in contact with water of organosilane layers formed by octadecyltrimethoxysilane (ODTMS) on polished aluminum alloy (AA2024) through dip-coating was studied by combining SEM, water contact angle measurements, and X-ray photoelectron spectroscopy. Similar organosilane layers were formed on AA2024 coated with permanganate conversion coating, 1,2-bis(triethoxysilyl)ethane (BTSE) and hydrated SiOx as under-layers, after which their long-term durability was also tested. During immersion in water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…However, this method may not be appropriate with other metals. For example, Kulinich et al [ 34 , 35 ] coated smooth aluminum surfaces with stearic acid. They found that upon long-term immersion in water, the aluminum surface with alkyl groups tended to gradually decay, which was caused by reactions with water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method may not be appropriate with other metals. For example, Kulinich et al [ 34 , 35 ] coated smooth aluminum surfaces with stearic acid. They found that upon long-term immersion in water, the aluminum surface with alkyl groups tended to gradually decay, which was caused by reactions with water.…”
Section: Resultsmentioning
confidence: 99%
“…However, this method may not be appropriate with other metals. For example, Kulinich et al [34,35] coated smooth aluminum surfaces with stearic acid. They found that upon The self-cleaning performance of the superhydrophobic surface was also investigated in this study.…”
Section: Applications Of the Superhydrophobic Surfacementioning
confidence: 99%
“…Namely, in continuous contact with the sessile water droplet, the stability of the fluorooxysilane layer against the hydrolysis-induced desorption of fluorooxysilane molecules from the coating/water interface can be studied. As shown earlier [48,49], the hydrolysis of siloxane bonds in fluorosilanes may cause the desorption of the hydrophobic molecules from the coating, exposing the hydroxyl groups, which are prone to hydration. As a result of this process, the superhydrophobic/hydrophobic state degrades.…”
Section: Resultsmentioning
confidence: 74%
“…Previous research has reported the long-term stability of OTS surfaces during water immersion. It was demonstrated that the WCA of the tested surfaces slightly dropped during a month of suspension in DI water, indicating that their hydrophobicity was not altered . Furthermore, this aspect could be explored to study the potential application of the persistent inhibitory effect of the OTS-coated materials on bacteria under different conditions.…”
Section: Resultsmentioning
confidence: 99%